Investigation of The impact of Unbalanced and Non-sinusoidal Supply Voltages on Converters - Hartungi, Rusdy (International Journal of Smart Grid and Sustainable Energy Technologies, 2018)
In this paper two input, current modulation strategies for matrix converters are experimentally analyzed under two different supply conditions: sinusoidal unbalanced voltages and non-sinusoidal balanced voltages. Both strategies use the Space Vector Modulation (SVM) technique in order to control the matrix converter accordingly to the input and output constraints. Strategy A modulates the input currents keeping the corresponding space vector in phase with the input voltage vector. Strategy B operates in order to keep the input current vector in phase with the positive sequence fundamental component of the input voltage vector. A comparison between the two strategies is made in terms of the reduction of the input current disturbances due to the unbalanced and non-sinusoidal voltage on the grid. It is found that a dynamic current modulation strategy, independent of the voltage disturbances such as Strategy B, is more effective for the reduction of the RMS value of input current disturbances. The validity of the theoretical investigation i.e. the effectiveness of the current modulation strategy conforms to experimental tests result carried out on a matrix converter prototype.